Arabic Listening Skill Test of 'Al-Arabiya Baina Yadaik Volume 1 and 2 Through Bloom's Taxonomy: Ikhtibār Mahārah al-Istimā’ bi al-Lugah al-‘Arabiyyah fī Kitab 'Al-Arabiya Baina Yadaik (1 & 2) ‘inda Mustawā Bloom - Mahmudi, Ihwan; Husna, Yukti Hikmatul; Wardani, Aisah Liana (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research aims to explore and explain the evaluation of Arabic language listening skills tests based on Bloom's Taxonomy, primarily focusing on utilizing the 'al-Arabiya Baina Yadaik' books in the first two volumes. This study utilizes a qualitative approach, specifically a descriptive analytical method, when the data is derived from literary sources. The primary focus of the data is 'Al-Arabiya Baina Yadaik Volumes 1 and 2, the books that serve as the focal point of analysis to understand content related to listening skills in Arabic. The data was obtained through an in-depth study of the content of 'Al-Arabiya Baina Yadaik books. The data collection method involves a comprehensive analysis of the text to identify question structures and difficulty levels according to Bloom's taxonomy. The analysis results indicate that listening skills tests based on Bloom's taxonomy, 'al-Arabiya Baina Yadaik' Volumes 1 and 2, suit beginner learners. In Volume 1, the remembering level (C1) has five types of test questions (33%), while the understanding level (C2) has 11 types (67%). In Volume 2, Remembering (C1) has one question (10%), Understanding (C2) has five questions (50%), Analysis (C4) has two questions (20%), and Evaluation (C6) has two questions (20%). This research contributes significantly to developing Arabic language listening skills tests and offers valuable guidance for educators in selecting appropriate teaching materials.